1992
DOI: 10.1056/nejm199201303260503
|View full text |Cite
|
Sign up to set email alerts
|

Resistance to Erythromycin in Group A Streptococci

Abstract: In Finland since 1988 there has been a rapid and substantial increase in resistance to erythromycin in group A streptococci. The extent of this resistance is particularly serious since there are only a few alternative antibiotics available for peroral treatment of group A streptococcal infections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
144
3
14

Year Published

1994
1994
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 321 publications
(169 citation statements)
references
References 27 publications
8
144
3
14
Order By: Relevance
“…Our results show that a few M types were responsible for up to 85% of the erythromycinresistant isolates, suggesting that few clones caused this phenomenon. This hypothesis was supported by the fact that the M phenotype was the most common resistance mechanism, a feature previously reported by other authors (20,23). However, genetic divergence among strains sharing the same emm gene sequence has been reported (5,6,17,29).…”
Section: Vol 41 2003 Emm Typing and Erythromycin Resistance Of S Psupporting
confidence: 63%
See 1 more Smart Citation
“…Our results show that a few M types were responsible for up to 85% of the erythromycinresistant isolates, suggesting that few clones caused this phenomenon. This hypothesis was supported by the fact that the M phenotype was the most common resistance mechanism, a feature previously reported by other authors (20,23). However, genetic divergence among strains sharing the same emm gene sequence has been reported (5,6,17,29).…”
Section: Vol 41 2003 Emm Typing and Erythromycin Resistance Of S Psupporting
confidence: 63%
“…Resistance to erythromycin remained at low levels among S. pyogenes in most countries of the world (14); however, in the last years, a significant increase in erythromycin-resistant isolates in different countries has been reported (15,20,22,23). In most of these studies, resistance to erythromycin was caused by a few clones and the mechanisms of resistance were mainly based on the presence of an active drug efflux by pumps encoded by the gene mefA (M phenotype) that take out of the cells 14-and 15-membered macrolides (25).…”
mentioning
confidence: 99%
“…However, most of the gramnegative bacteria isolated were resistant to macrolides. These results were similar to the study reported by Seppala et al 24 The resistance shown to macrolides might be due to frequent and large administration. In addition, they were used in prophylaxis treatment.…”
Section: Discussionsupporting
confidence: 92%
“…29 In 1992, Seppala et al, reported a high rate of erythromycin resistance(>45%) in Finland. 30 High frequencies of Erythromycin resistance have also been reported from Spain (21.3%), Italy (22.6%), Greece (24%), France (22.4%), Portugal (26.6%)and USA(32%). 31 Although there have been recent isolated reports of macrolide resistance in the United States, there is no evidence that this is widespread at the present time, as less than 5% of Group A streptococci isolates in the United States have been shown to be resistant to Erythromycin.…”
mentioning
confidence: 97%